IMPACT OF UTILIZATION OF FACEBOOK GROUP PAGE AS AN INSTRUCTIONAL TOOL ON UNIVERSITY STUDENTS’ ACADEMIC PERFORMANCE: A PRELIMINARY STUDY - Lacap, Jean Paolo (PEOPLE: International Journal of Social Sciences, 2015)
The study aims to identify how the utilization of Face book group page affects the academic performance of university students. It is assumed that academic performance is affected by student engagement, independent learning, and critical thinking. The participants of the study were 81 Bachelor of Science in Business Administration major in Management and Entrepreneurship (BSBA M&E) of a higher education institution in Angeles City, Philippines who took Business Plan course in second semester, 2014-2015. Using correlation and multiple regression analyses the findings revealed that only student engagement has a statistically significant predictive impact or effect on respondents’ academic performance. Moreover, the contributions of independent learning and critical thinking are not statistically significant and both are not significant predictors of academic performance.